2023
DOI: 10.1039/d3se00679d
|View full text |Cite
|
Sign up to set email alerts
|

Strong coupling effect induced surface reconstruction of CeF3–Ni3N to form CeF3–NiOOH for the oxygen evolution reaction

Abstract: Electrocatalytically active interface in a heterostructure is extremely crucial to obtain optimum adsorption energy of intermediates (O*, OH*, and HOO*) and faster electron transfer. Due to the slow kinetics of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Figure b shows hybrid nanoparticles of Co 4 N–Ni 3 N, which are in line with the morphology obtained by SEM analysis. Figure c depicts the HRTEM image of the catalyst where 0.17 nm is the fringe width that corresponds to the (200) plane of cubic Co 4 N (Figure d), and the other 0.203 nm is related to the (111) plane of hexagonal Ni 3 N (Figure e). We observed the construction of an interface between Co 4 N and Ni 3 N in the HRTEM images. The charge is transferred from the Co 4 N phase to the Ni 3 N phase with the assistance of these heterojunctions.…”
Section: Resultsmentioning
confidence: 85%
“…Figure b shows hybrid nanoparticles of Co 4 N–Ni 3 N, which are in line with the morphology obtained by SEM analysis. Figure c depicts the HRTEM image of the catalyst where 0.17 nm is the fringe width that corresponds to the (200) plane of cubic Co 4 N (Figure d), and the other 0.203 nm is related to the (111) plane of hexagonal Ni 3 N (Figure e). We observed the construction of an interface between Co 4 N and Ni 3 N in the HRTEM images. The charge is transferred from the Co 4 N phase to the Ni 3 N phase with the assistance of these heterojunctions.…”
Section: Resultsmentioning
confidence: 85%
“…When considering this aspect, nickel (Ni)-based catalysts exhibit significant promise among the economically viable transition metals owing to the presence of high valence state Ni-intermediates, which play an essential role in both the oxygen evolution reaction (OER) and the urea oxidation reaction (UOR). [6,29,30] Extensive research has demonstrated that Ni and Ni-based compounds undergo oxidation to form nickel's active state (NiOOH) in an alkaline medium, thereby serving as catalysts for the urea oxidation reaction (UOR). [31] Furthermore, Feng et al have discovered that optimizing the ratio of Ni 2 + / Ni 3 + content can maximize the catalytic performance for urea oxidation.…”
Section: Introductionmentioning
confidence: 99%